2018
DOI: 10.3847/1538-3881/aac5de
|View full text |Cite
|
Sign up to set email alerts
|

Masses and Radii of Four Very Low-mass Stars in F+M Eclipsing Binary Systems

Abstract: Eclipsing Binaries (EBs) with one of the companions as very low mass stars (VLMS or M dwarfs) are testbeds to substantiate stellar models and evolutionary theories. Here, we present four EB candidates with F type primaries, namely, SAO 106989, HD 24465, EPIC 211682657 and HD 205403, identified from different photometry missions, SuperWasp, KELT, Kepler 2 (K2) and STEREO. Using the highresolution spectrograph, PARAS, at the 1.2 m telescope at Mount Abu, Rajasthan, India, we hereby report the detection of four V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 125 publications
(118 reference statements)
1
14
0
Order By: Relevance
“…The double-lined eclipsing binaries (DEBs) provide a direct, fundamental test of the models because they yield radii at a given mass. Again it has long been known that the eclipsing binaries show that M-star E-mail: smorrell@astro.ex.ac.uk radii appear to be inflated for their mass (see for example Figure 2 of Chen et al 2014;Chaturvedi et al 2018;Parsons et al 2018;Mann et al 2019), though Torres (2013) highlighted that the effect is subtle. Furthermore there can be significant discrepancies between parameter determinations for the same binary, see for example the discussion of T-Cyg1-12664 in Han et al (2017), or the difference in measured radius for the secondary in PTFEB132.707+19.810/AD 3814 (Kraus et al 2017;Gillen et al 2017).…”
Section: Measuring the Radii Of M-dwarfsmentioning
confidence: 99%
“…The double-lined eclipsing binaries (DEBs) provide a direct, fundamental test of the models because they yield radii at a given mass. Again it has long been known that the eclipsing binaries show that M-star E-mail: smorrell@astro.ex.ac.uk radii appear to be inflated for their mass (see for example Figure 2 of Chen et al 2014;Chaturvedi et al 2018;Parsons et al 2018;Mann et al 2019), though Torres (2013) highlighted that the effect is subtle. Furthermore there can be significant discrepancies between parameter determinations for the same binary, see for example the discussion of T-Cyg1-12664 in Han et al (2017), or the difference in measured radius for the secondary in PTFEB132.707+19.810/AD 3814 (Kraus et al 2017;Gillen et al 2017).…”
Section: Measuring the Radii Of M-dwarfsmentioning
confidence: 99%
“…Mass-radius diagram for eclipsing M-dwarfs. The M-dwarf companion of TIC-231005575 is shown in red, with eclipsing M-dwarfs from the EBLM project in blue, and M-dwarfs with mass and radius measurements with less than 10% uncertainty (from Table 4 of Chaturvedi et al (2018), and references therein) in black. We also show the mass and radius of TIC-238855958 (Gill et al 2020) in green.…”
Section: The Tic-231005575 Systemmentioning
confidence: 99%
“…Finally, we note that the radius, stellar inclination, and projected rotational velocity of KELT J072709 + 072007A that we infer from our global analysis implies a rotation period of approximately 0.8 d. Some studies of F-M binaries (e.g. Fernandez et al 2009;Chaturvedi et al 2018) assume tidal synchronization of the primary star to obtain the M dwarf's mass and radius in a 'model-independent' way. As the extreme example of KELT J072709 + 072007 shows and as Fernandez et al (2009) found for one of their F-M EBs, this assumption may not hold for stars that experience inefficient tidal braking due to the absence of a substantial convective envelope, and caution must be exercised when applying this assumption to mainsequence stars above the Kraft break at T eff ≈ 6250 K.…”
Section: Low-mass Companions To Intermediate-mass Starsmentioning
confidence: 57%